PERAN PENGGUNAAN SEARCH ENGINE OPTIMIZATION DAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DALAM MENINGKATKAN MINAT BELI E-COMMERCE ELEVENIA PADA MAHASISWA KABUPATEN PURWAKARTA - indra maulana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of search engine optimization as a promotional media in increasingbuying interest e-commerce Elevenia, to determine the effect of social media as a promotional media in increasingbuying interest e-commerce Elevenia, and the role of using search engine optimization and social media as media. promotion in increasing interest in buying e-commerce Elevenia in Purwakarta Regency students. This study uses a quantitative research model, with the method used in the research is quantitative descriptive method and a sample of 99 respondents from high school students residing in Purwakarta Regency. This research shows that Search Engine Optimization has a significant effect on increasingBuying Interest E-Commerce Elevenia's, then social media has a significant real effect on increasingPurchase Interest E-Commerce Elevenia's, and for bothvariables. searchengine optimization and social media as promotional media in increasing interest in buying e-commerce Elevenia in Purwakarta Regency students.